Effect of temperature on the growth, survival, development and foraging behaviour of Sardina pilchardus larvae - Garrido, Susana (2020)
The effect of water temperature on the growth, survival, development and foraging behaviour of European sardine Sardina pilchardus larvae was examined in the laboratory. First, the capability of early sardine larvae to cope with starvation was assessed at temperatures from 10 to 22°C. Second, we examined under ad libitum feeding conditions and across the range of temperatures experienced by sardines during spawning along the Atlanto-Iberian coast (13-17°C) the ontogenetic changes in growth, survival and foraging behaviour of sardine larvae. Unfed larvae had similar maximum survival times (11-12 d post hatching, dph) from 13 to 15°C, but the survival time was significantly shorter at the coldest and warmest temperatures tested. The survival of exogenously feeding larvae increased with temperature, but younger endogenously feeding larvae had higher survival at colder temperatures. The cumulative mortality after 25 dph, however, was similar at the 3 temperatures. Not only larval growth rate increased with increasing temperature, but ontogenetic development also occurred sooner and at smaller sizes. Notochord flexion, which is a developmental milestone for fish, occurred 10 d earlier at 17 rather than at 13°C. The time spent swimming and the foraging behaviour (orientations to prey, feeding strikes and successful capture) significantly increased throughout the ontogeny and with temperature. This study highlights how even modest changes in spawning temperature can lead to large changes in the survival and growth of larval sardine. This study also reveals some of the mechanisms whereby inter-annual and seasonal variability in temperature can have significant ecological impacts at the population level.